Ketidakseragaman Sebaran Spasial Variabilitas Musiman Eddy di Perairan Barat Laut Indonesia - Kartadikaria, Aditya Rakhmat; Napitupulu, Gandhi; Rangga, Kalaka; Radjawane, Ivonne Milichristi; Abdullah, Faizal Ade Rahmahuddin (Jurnal Kelautan Tropis, 2024)
Sea level anomaly (SLA) data spanning from 1993 – 2022 were used to analyze the characteristic of eddy current in Northwest Indonesian. An improved winding angle method was used and was able to detect 1663 anticyclonic eddies (AEs) and 1748 cyclonic eddies (CEs). The average eddy lifespan is approximately four weeks. The eddy in the West Indonesian Ocean has a radius ranging from 40 – 100 km and a high number of mesoscale eddy (radius more than 100 km) detected in the northern area of West Indonesian Ocean (4° N - 10° N). The eddy kinetic energy (EKE) increased proportionally with their radius, whereas the eddy vorticity decreased proportionally with their increasing radius. The seasonal cycles of eddy circulation in the west Indonesian Ocean were differ for both AEs and CEs, where AEs were dominated during east monsoon season (JJA) and CEs came with longer periods from November to March, yet for both AEs and CEs they have similar radius per month. During weak periods of both eddies, their meridional distributions differ; CEs tend to be formed in relatively lower latitude, while AEs were concentrated in relatively higher latitude. Data anomali permukaan laut/sea level anomaly (SLA) dalam kurun waktu 1993 – 2022 digunakan untuk mempelajari karakteristik sirkulasi arus eddy di perairan barat laut Indonesia. Metode Winding Angles yang telah dimodifikasi mampu mendeteksi 1663 anticyclonic eddies (AE) dan 1748  cyclonic eddies (CE). Rata-rata umur eddy yang terdeteksi adalah sekitar empat minggu. Mayoritas sirkulasi arus eddy memiliki radius 40 – 100 km dan eddy dengan radius berskala meso (lebih dari 100 km) banyak terkonsentrasi di bagian utara (4° N - 10° N) perairan barat laut Indonesia. Nilai energi kinetik eddy (EKE) bertambah sebanding dengan pertambahan radius, sedangkan nilai vortisitas berbanding terbalik dengan radius. Sirkulasi arus eddy di perairan barat laut Indonesia pada musim timur (JJA) didominasi oleh AE , sedangkan CE mendominasi di musim barat (DJF) dengan periode yang lebih panjang dari November hingga Maret, namun dengan rata-rata radius yang sama setiap bulannya. Pada saat periode di mana kejadian eddy minimum, ditemukan perbedaan letak distribusi meridional eddy bervortisitas tinggi yang menunjukkan CE lebih didukung pembentukannya pada lintang yang lebih rendah daripada AE.